Hippocampal mossy fiber long-term depression in Grm2/3 double knockout mice. - Lyon, L; Borel, M; Carrión, M; Kew, J; Corti, C; Harrison, P; Burnet, P; Paulsen, O; Rodríguez-Moreno, A (2011)
Group II metabotropic glutamate receptors (mGluR2, encoded by Grm2, and mGluR3, encoded by Grm3) are inhibitory autoreceptors that negatively modulate the adenylate cyclase signaling cascade. Within the hippocampus, mGluR2 is believed to play a key role in the induction of long-term depression (LTD) at mossy fiber-CA3 synapses. Here, we used Grm2/3 double knockout (dko) mice to investigate to what extent group II mGluRs are necessary for mossy fiber LTD. Surprisingly, we found that these mice displayed prominent mossy fiber LTD. However, the induction of this form of LTD was sensitive to the external Ca(2+) concentration. Mossy fiber LTD in Grm2/3 dko mice was indistinguishable from that in wild-type mice at 4 mM Ca(2+) , but largely absent at 2 mM external Ca(2+) . Mossy fiber LTD in Grm2/3 dko mice was not blocked by the N-methyl-D-aspartic acid (NMDA) receptor antagonist D-AP5, confirming that the observed response did not reflect NMDA receptor-dependent LTD in contaminating associational-commissural fibers, and enabling us to use the NMDA receptor-mediated EPSC to monitor mossy fiber LTD. Using whole-cell recordings, we demonstrated that LTD of the NMDA receptor-mediated EPSC in Grm2/3 dko mice was not affected by intracellular application of BAPTA and CsF to block postsynaptic Ca(2+) and G-protein-mediated effects. This presynaptic LTD was, however, blocked by the AMPA/kainate receptor antagonist, NBQX. Thus, an activity-dependent, external Ca(2+) concentration-sensitive form of mossy fiber LTD can be induced in Grm2/3 dko mice. Two mGluR antagonists also failed to block mossy fiber LTD under 4 mM conditions in wild-type mice, strengthening the conclusion that group II mGluRs are not obligatory for mossy fiber LTD.